Developing an Innovative Method for Visual Perception Evaluation in a Physical-Based Virtual Environment. (September 2019) - Abd-Alhamid, Fedaa; Kent, Michael; Bennett, Christopher; Calautit, John; Wu, Yupeng
Abstract: With the developments in virtual reality technologies, significant researches have been conducted for human response on indoor luminous environment using head-mounted display to replace those in real environment. However, the limited resolution and luminance values offered by the devices might affect the perceived appearance and high-order impressions in the simulated virtual environment. In this study, a simulated 3-dimensional virtual office was compared against a real one. Both settings presented similar physical and luminous conditions to twenty participants (N = 20). The study investigated subjective and objective visual responses and participants' interaction with the virtual environment based on measurements of perceived presence. Subjective assessments included questions on luminous environment appearance (brightness, colour-temperature, distribution) and high-order perceptions (pleasantness, interest, spaciousness, excitement and complexity). Objective assessments measured contrast-sensitivity and colour-discrimination tasks to assess visual performance across the two representation environments. Results showed no significant differences between the two environments based on the studied parameters, indicating a high level of perceptual accuracy of appearance and high-order perceptions. Minor physical symptoms related to the headset use and high level of perceived presence were found, indicating the proposed methodology's capability to provide realistic immersive environments. Although attributes regarding scene quality: colours, details, and contrast were perceived significantly different to the real environment, objective tasks showed that similar contrast and colour appearance can be produced in the virtual environment with minor impact on fine-details due to limited resolution. Virtual reality maybe a promising alternative representation medium to investigate visual perceptions as the overall appearance of the scene can still be correctly acquired. Graphical abstract: Image 1 Highlights: Virtual physically-based luminous environment was assessed against a real one. Perceptual accuracy of appearance and high order perceptions were comparable. Details, contrast, and colours were perceived subjectively significantly different. Tasks visual performance presented a comparable appearance of colour and contrast. The proposed method looks promising to investigate real luminous environments.